PENINGKATAN PENGETAHUAN ASI BAGI IBU MENYUSUI DI KECAMATAN ARJASA SITUBONDO MELALUI PELATIHAN PEMBUATAN JAMU SERBUK - Yunita Handoyo, Diana Lady; Atiqah, Sri Nur; Adzkiyah, Siti Zamilatul (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
Jamu is an Indonesian cultural heritage which is used as a traditional medicine. As one of the representations of local wisdom in Indonesia, herbal medicine has developed in society with various benefits and dosage forms. The people of Arjasa District, Situbondo Regency use herbal ingredients to increase milk production in the form of herbs. Herbal medicine has several weaknesses, one of which is the bitter taste it causes when consumed, so one of the solutions given is to make herbal preparations in the form of herbal granules. The purpose of this activity is to provide insight and skills for breastfeeding mothers regarding the processing of herbal medicine granules. The result of this activity was that 100% of respondents stated that this activity provided benefits for breastfeeding mothers in processing herbal medicine.